Participation in Country Economic and Sector Work - Aronson, Dan R. (World Bank, Washington, DC, 2012)
Using a participatory approach in the Bank ' s country economic and sector work may involve extra costs, as well as some loss of control over timing and quality of work. Experience suggests, however, that these costs are more than offset by substantial benefits, including improvements in the Bank-borrower relationship, speedier acceptance of recommendations, both by the Bank and the borrower, and increased in-country capacity for policy research and analysis.